8‐Prenylnaringenin tissue distribution and pharmacokinetics in mice and its binding to human serum albumin and cellular uptake in human embryonic kidney cells. Issue 4 (22nd January 2022) - Tanaka, Yoshiaki; Okuyama, Hitomi; Nishikawa, Miyu; Ikushiro, Shin‐ichi; Ikeda, Mayumi; Ishima, Yu; Ukawa, Yuichi; Oe, Kenichi; Terao, Junji; Mukai, Rie
Abstract: 8‐Prenylnaringenin (8‐PN), a hop flavonoid, is a promising food substance with health benefits. Compared with nonprenylated naringenin, 8‐PN exhibits stronger estrogenic activity and prevents muscle atrophy. Moreover, 8‐PN prevents hot flushes and bone loss. Considering that prenylation reportedly improves the bioavailability of flavonoids, we compared the parameters related to the bioavailability [pharmacokinetics and tissue distribution in C57/BL6 mice, binding affinity to human serum albumin (HSA), and cellular uptake in HEK293 cells] of 8‐PN and its mother (non‐prenylated) compound naringenin. C57/BL6 mice were fed an 8‐PN or naringenin mixed diet for 22 days. The amount of 8‐PN (nmol/g tissue) in the kidneys (16.8 ± 9.20), liver (14.8 ± 2.58), muscles (3.33 ± 0.60), lungs (2.07 ± 0.68), pancreas (1.80 ± 0.38), heart (1.71 ± 0.27), spleen (1.36 ± 0.29), and brain (0.31 ± 0.09) was higher than that of naringenin. A pharmacokinetic study in mice demonstrated that the C max of 8‐PN (50 mg/kg body weight) was lower than that of naringenin; however, the plasma concentration of 8‐PN 8 h after ingestion was higher than that of naringenin. The binding affinity of 8‐PN to HSA and cellular uptake in HEK293 cells were higher than those of naringenin. 8‐PN bioavailability features assessed in mouse or human model experiments were obviously different from those of naringenin. Abstract : This study aimed to compare the parameters related to the bioavailability of 8‐PN and its mother (nonprenylated) compound naringenin. The tissue distribution of 8‐PN in mice was higher than that of naringenin. Compared with naringenin, 8‐PN showed a stronger affinity to human serum albumin and higher cellular uptake in human embryonic kidney cells.